Percutaneous repair or medical treatment for secondary mitral regurgitation: outcomes at 2 years. (18th November 2019) - Iung, Bernard; Armoiry, Xavier; Vahanian, Alec; Boutitie, Florent; Mewton, Nathan; Trochu, Jean‐Noël; Lefèvre, Thierry; Messika‐Zeitoun, David; Guerin, Patrice; Cormier, Bertrand; Brochet, Eric; Thibault, Hélène; et al.
Abstract: Aims: The MITRA‐FR trial showed that among symptomatic patients with severe secondary mitral regurgitation, percutaneous repair did not reduce the risk of death or hospitalization for heart failure at 12 months compared with guideline‐directed medical treatment alone. We report the 24‐month outcome from this trial. Methods and results: At 37 centres, we randomly assigned 304 symptomatic heart failure patients with severe secondary mitral regurgitation (effective regurgitant orifice area >20 mm 2 or regurgitant volume >30 mL), and left ventricular ejection fraction between 15% and 40% to undergo percutaneous valve repair plus medical treatment (intervention group, n  = 152) or medical treatment alone (control group, n  = 152). The primary efficacy outcome was the composite of all‐cause death and unplanned hospitalization for heart failure at 12 months. At 24 months, all‐cause death and unplanned hospitalization for heart failure occurred in 63.8% of patients (97/152) in the intervention group and 67.1% (102/152) in the control group [hazard ratio (HR) 1.01, 95% confidence interval (CI) 0.77–1.34]. All‐cause mortality occurred in 34.9% of patients (53/152) in the intervention group and 34.2% (52/152) in the control group (HR 1.02, 95% CI 0.70–1.50). Unplanned hospitalization for heart failure occurred in 55.9% of patients (85/152) in the intervention group and 61.8% (94/152) in the control group (HR 0.97, 95% CI 0.72–1.30). Conclusions: In patients with severe secondary mitral regurgitation, percutaneous repair added to medical treatment did not significantly reduce the risk of death or hospitalization for heart failure at 2 years compared with medical treatment alone.